Effect of Ginger Extract in Lowering Blood Pressure in The Elderly with Hypertension - Ulkomah Ulkomah; Desridius Chalid; Farida Murtiani; Aninda Dinar Widiantari (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Hypertension is a cardiovascular disease that is common to find in elderly. Its prevalence reached to 22% throughout the world in 2020. Pharmacological treatment to hypertension involves lifetime commitment to drug adherence. Ginger extract as complementary therapy has been widely common in Indonesia to reduce common flu symptoms and indigestion. It acts as a therapeutic effect that boosts immune system, improving the cardiovascular system by reducing the level of low-density lipoproteins and cholesterol. Prior studies showed its effect in lowering blood pressure in hypertension patients, while several other said the effect was stronger in less than 50 years old people. The aim of the study was to analyze red ginger extract as main therapy in hypertension in elderly. Methods: This study was a quasi-experimental with one group pretest-posttest without control group. Participants were 45-65 years old hypertension patients in Semper Barat II Primary Health Care. Intervention was 4 grams of minced ginger then added by 2 spoons of honey in 100 ml of water. The drink was consumed in 5 days. Results: Average age of participants were 62,9 (60-65) years old. Before intervention, mean blood pressure was 156,8 (140-180) / 98,03 (85-115) mmHg and lowered to 148,6 (125-170) / 92,57 (80-110) mmHg after 5 days of intervention (p=0,0001). Conclusion: We recommend ginger extract as an alternative to reduce blood pressure in elderly with hypertension. We hoped the results will become a new approach to treat hypertension.